Measuring the Dielectric Constant of Paper Using a Parallel Plate Capacitor - Vanja Mandrić Radivojević; Rupčić, Slavko; Srnović, Mario; Benšić, Goran (International Journal of Electrical and Computer Engineering Systems, 2018)
This article is a result of measuring the dielectric constant of a dielectric used in studying the influence of dielectrics on the antennae reflection coefficients. A paper having a density of 0.797 g/cm3, moisture content of 0% and temperature of 210C, is used as a dielectric. Although the literature provides a lot of data on the dielectric properties of wood and paper, without direct measurement of the dielectric constant it is impossible to know its amount for the dielectric used in the defined frequency range. Dielectric constant measurements are performed in the frequency range from 100 Hz to 100 kHz, while the frequency range of its impact on the aperture antenna reflection coefficients is up to 2 GHz. The frequency range from 100 KHz to 10 GHz is interpolated and fitted by using measurements and available literature data and by respecting physical influences and phenomena and functional changes of the dielectric constant of paper within the given range.